The Prevalence of Metabolic Syndrome According to Grip Strength in Teenagers - Duk Han Ko; Young Kyun Kim (MDPI AG, 2021)
The prevalence of metabolic syndrome in adolescents is increasing. Recently, the relevance of grip strength as a factor of metabolic syndrome in this population has raised questions. This study investigated the prevalence of metabolic syndrome according to grip strength in children and adolescents using large-scale data from the Korean National Health and Nutrition Survey (KNHNS). From 2014 to 2018, 1527 boys and 1292 girls participated in the KNHNS. The participants were classified into three groups according to age: 10-12 years (early teenager, ET), 13-15 years (middle teenager, MT), and 16-18 years (late teenager, LT). The participants were classified as having metabolic syndrome if they fulfilled three of the adolescent metabolic syndrome criteria. The grip strength was divided into groups with high and low grip strength, respectively, and the cutoff value for the prevalence was calculated using receiver operating characteristic curve analysis. There were significant differences in waist circumference, high-density lipoprotein cholesterol, and triglyceride levels based on grip strength in the ET, MT, and LT groups. Therefore, the prevalence of metabolic syndrome was lower when grip strength was higher. The cut-off values of the relative grip strength (kg/body weight) to predict metabolic syndrome among boys were 0.349, 0.466, and 0.485 for the ET, MT, and LT groups, respectively. The corresponding cut-off values for girls were 0.373, 0.383, and 0.382, respectively. In conclusion, there is a non-linear relationship between grip strength and metabolic syndrome in adolescents.